Risk environments facing potential users of a supervised injection site in Ottawa, Canada - Shaw, Ashley; Lazarus, Lisa; Pantalone, Tyler; LeBlanc, Sean; Lin, Dolly; Stanley, Daina; Chepesiuk, Caleb; Patel, Sheetal; Tyndall, Mark (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Supervised injection sites (SISs) have been effective in reducing health risks among people who inject drugs (PWID), including those who face issues of homelessness, mental health illness, interactions with local policing practices, and HIV infection. We investigate the risk behaviours and risk environments currently faced by potential users of an SIS in Ottawa to establish the need for such a service and to contribute to the design of an SIS that can address current health risks and reduce harm. Methods The PROUD cohort is a community-based participatory research (CBPR) project that examines the HIV risk environment among people who use drugs in Ottawa. From March to October 2013, 593 people who reported using injection drugs or smoking crack cocaine were enrolled through street-based recruitment in the ByWard Market neighbourhood, an area of the city with a high concentration of public drug use and homelessness. Participants completed a demographic, behavioural, and risk environment questionnaire and were offered HIV point-of-care testing. We undertook descriptive and univariate analyses to estimate potential use of an SIS by PWID in Ottawa and to explore risk behaviours and features of the risk environment faced by potential users of the service. Results Of those participants who reported injecting drugs in the previous 12 months (n = 270), 75.2 % (203) reported a willingness to use an SIS in Ottawa. Among potential SIS users, 24.6 % had recently injected with a used needle, 19.0 % had trouble accessing new needles, 60.6 % were unstably housed, 49.8 % had been redzoned by the police, and 12.8 % were HIV positive. Participants willing to use an SIS more frequently injected in public (OR = 1.98, 95 % CI = 1.06–3.70), required assistance to inject (OR = 1.84, 95 % CI = 1.00–3.38), were hepatitis C positive (OR = 2.13, 95 % CI = 1.16–3.91), had overdosed in the previous year (OR = 2.00, 95 % CI = 1.02–3.92), and identified as LGBTQ (OR = 5.61, 95 % CI = 1.30–24.19). Conclusion An SIS in Ottawa would be well-positioned to reach its target group of highly marginalized PWID and reduce drug-related harms. The application of CBPR methods to a large-scale quantitative survey supported the mobilization of communities of PWID to identify and advocate for their own service needs, creating an enabling environment for harm reduction action.